Invariable hydraulics and rapidly tapering cross-sectional areas of lateral roots reduce water transport capacity to half at the crown periphery of mature Scots pine - Donggyu Kam; Teemu Hölttä; Annikki Mäkelä; Frank Berninger; Yann Salmon; Tuomo Kalliokoski; Anna Lintunen; Ram Oren (Agricultural and Forest Meteorology, 2026)

Predictors of 30-day readmission in patients with bloodstream infection: a population-based cohort study - Kim Oren Gradel; Pavithra Laxsen Anru; Stig Lønberg Nielsen; Sofie Skovmand; Ram Benny Dessau; Jens Kjølseth Møller; Steen Lomborg Andersen; Thøger Gorm Jensen; John Eugenio Coia; Mette Søgaard (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Increasing pathlength resistance and within-canopy shading similarly attenuate transpiration in accruing collocated stands of five pine species - Chainey A. Boroski; Chris A. Maier; Sari Palmroth; Jean-Christophe Domec; Yi Wang; Ram Oren (Agricultural and Forest Meteorology, 2026)

Regulation of tree water use by biophysical factors: Insights based on multi-layer hierarchical residual analysis - Jiali Du; Ram Oren; Teemu Hölttä; Shaoyuan Feng; Weishu Wang; Xiaoqin Dai; Zailin Huo (Journal of Hydrology, 2025)

Carbon allocation to roots of suppressed Norway spruce increases immediately after selection harvest - Aleksi Lehtonen; Juha Heikkinen; Chainey A. Boroski; Olli-Pekka Tikkasalo; Katja T. Rinne-Garmston; Elina Sahlstedt; Mika Korkiakoski; Anna Kärkönen; Anna Lintunen; Harri Mäkinen; Mikko Peltoniemi; Gonzalo de Quesada; et al. (Forest Ecology and Management, 2025)

Similar response of canopy conductance to increasing vapor pressure deficit and decreasing soil conductivity with drought among five morphologically contrasting but co-occurring pine species - Haoyu Zhang; Jean-Christophe Domec; Christopher A. Maier; Chainey A. Boroski; Na Wang; Sari Palmroth; Ram Oren (Agricultural and Forest Meteorology, 2025)

Extramatrical mycelial biomass is mediated by fine root mass and ectomycorrhizal fungal community composition across tree species - Lulu Xie; Sari Palmroth; Chunying Yin; Ram Oren (Science of The Total Environment, 2024)

Hyposensitive canopy conductance renders ecosystems vulnerable to meteorological droughts - Hang Xu; Zhiqiang Zhang; Ram Oren; Xiaoyun Wu (Global Change Biology, 2023)
Increased meteorological drought intensity with rising atmospheric demand for water (hereafter vapor pressure deficit [VPD]) increases the risk of tree mortality and ecosystem dysfunction worldwide. Ecosystem‐scale water‐use strategy is increasingly recognized as a key factor in regulating drought‐related ecosystem responses. However, the link between water‐use strategy and ecosystem vulnerability to meteorological droughts is poorly established. Using the global flux observations, historic hydroclimatic data, remote‐sensing products, and plant functional‐trait archive, we identified potentially vulnerable ecosystems, examining how ecosystem water‐use strategy, quantified by the percentage bias ( δ ) of the empirical canopy conductance sensitivity to VPD relative to the theoretical value, mediated ecosystem responses to droughts. We found that prevailing soil water availability substantially impacted δ in dryland regions where ecosystems with insufficient soil moisture usually showed conservative water‐use strategy, while ecosystems in humid regions exhibited more pronounced climatic adaptability. Hyposensitive and hypersensitive ecosystems, classified based on δ falling below or above the theoretical sensitivity, respectively, achieved similar net ecosystem productivity during droughts, employing different structural and functional strategies. However, hyposensitive ecosystems, risking their hydraulic system with a permissive water‐use strategy, were unable to recover from droughts as quickly as hypersensitive ones. Our findings highlight that processed‐based models predicting current functions and future performance of vegetation should account for the greater vulnerability of hyposensitive ecosystems to intensifying atmospheric and soil droughts.

The response of coarse root biomass to long‐term CO 2 enrichment and nitrogen application in a maturing Pinus taeda stand with a large broadleaved component - Chris A. Maier; Kurt H. Johnsen; Pete H. Anderson; Sari Palmroth; Dohyoung Kim; Heather R. McCarthy; Ram Oren (Global Change Biology, 2022)
Elevated atmospheric CO 2 (eCO 2 ) typically increases aboveground growth in both growth chamber and free‐air carbon enrichment (FACE) studies. Here we report on the impacts of eCO 2 and nitrogen amendment on coarse root biomass and net primary productivity (NPP) at the Duke FACE study, where half of the eight plots in a 30‐year‐old loblolly pine ( Pinus taeda , L.) plantation, including competing naturally regenerated broadleaved species, were subjected to eCO 2 (ambient, aCO 2 plus 200 ppm) for 15–17 years, combined with annual nitrogen amendments (11.2 g N m −2 ) for 6 years. Allometric equations were developed following harvest to estimate coarse root (>2 mm diameter) biomass. Pine root biomass under eCO 2 increased 32%, 1.80 kg m −2 above the 5.66 kg m −2 observed in aCO 2 , largely accumulating in the top 30 cm of soil. In contrast, eCO 2 increased broadleaved root biomass more than twofold (aCO 2 : 0.81, eCO 2 : 2.07 kg m −2 ), primarily accumulating in the 30–60 cm soil depth. Combined, pine and broadleaved root biomass increased 3.08 kg m −2 over aCO 2 of 6.46 kg m −2 , a 48% increase. Elevated CO 2 did not increase pine root:shoot ratio (average 0.24) but increased the ratio from 0.57 to 1.12 in broadleaved species. Averaged over the study (1997–2010), eCO 2 increased pine, broadleaved and total coarse root NPP by 49%, 373% and 86% respectively. Nitrogen amendment had smaller effects on any component, singly or interacting with eCO 2 . A sustained increase in root NPP under eCO 2 over the study period indicates that soil nutrients were sufficient to maintain root growth response to eCO 2 . These responses must be considered in computing coarse root carbon sequestration of the extensive southern pine and similar forests, and in modelling the responses of coarse root biomass of pine–broadleaved forests to CO 2 concentration over a range of soil N availability.

How tree species, tree size, and topographical location influenced tree transpiration in northern boreal forests during the historic 2018 drought - Jose Gutierrez Lopez; Pantana Tor‐ngern; Ram Oren; Nataliia Kozii; Hjalmar Laudon; Niles J. Hasselquist (Global Change Biology, 2021)
Trees in northern latitude ecosystems are projected to experience increasing drought stress as a result of rising air temperatures and changes in precipitation patterns in northern latitude ecosystems. However, most drought‐related studies on high‐latitude boreal forests (>50°N) have been conducted in North America, with few studies quantifying the response in European and Eurasian boreal forests. Here, we tested how daily whole‐tree transpiration ( Q , Liters day −1 ) and Q normalized for mean daytime vapor pressure deficit ( Q DZ , Liters day −1 kPa −1 ) were affected by the historic 2018 drought in Europe. More specifically, we examined how tree species, size, and topographic position affected drought response in high‐latitude mature boreal forest trees. We monitored 30 Pinus sylvestris (pine) and 30 Picea abies (spruce) trees distributed across a topographic gradient in northern Sweden. In general, pine showed a greater Q DZ control compared to spruce during periods of severe drought (standardized precipitation–evapotranspiration index: SPEI Q DZ reductions (using non‐drought Q DZ as reference) were less pronounced in larger trees during severe drought, but there was a species‐specific pattern: Q DZ reductions were greater in pine trees at high elevations and greater in spruce trees at lower elevations. Despite lower Q DZ during severe drought, drought spells were interspersed with small precipitation events and overcast conditions, and Q DZ returned to pre‐drought conditions relatively quickly. This study highlights unique species‐specific responses to drought, which are additionally driven by a codependent interaction among tree size, relative topographic position, and unique regional climate conditions.

Evapotranspiration and water yield of a pine‐broadleaf forest are not altered by long‐term atmospheric [CO 2 ] enrichment under native or enhanced soil fertility - Eric J. Ward; Ram Oren; Hyun Seok Kim; Dohyoung Kim; Pantana Tor‐ngern; Brent E. Ewers; Heather R. McCarthy; Andrew Christopher Oishi; Diane E. Pataki; Sari Palmroth; Nathan G. Phillips; Karina V. R. Schäfer (Global Change Biology, 2018)
Changes in evapotranspiration ( ET ) from terrestrial ecosystems affect their water yield ( WY ), with considerable ecological and economic consequences. Increases in surface runoff observed over the past century have been attributed to increasing atmospheric CO 2 concentrations resulting in reduced ET by terrestrial ecosystems. Here, we evaluate the water balance of a Pinus taeda (L.) forest with a broadleaf component that was exposed to atmospheric [CO 2 ] enrichment (ECO 2 ; +200 ppm) for over 17 years and fertilization for 6 years, monitored with hundreds of environmental and sap flux sensors on a half‐hourly basis. These measurements were synthesized using a one‐dimensional Richard's equation model to evaluate treatment differences in transpiration ( T ), evaporation ( E ), ET , and WY . We found that ECO 2 did not create significant differences in stand T, ET , or WY under either native or enhanced soil fertility, despite a 20% and 13% increase in leaf area index, respectively. While T , ET , and WY responded to fertilization, this response was weak ( E responded to ECO 2 in the first 7 years of the study, this effect was of negligible magnitude ( P. taeda , our results imply that recent observations of increased global streamflow cannot be attributed to decreases in ET across all ecosystems, demonstrating a great need for model–data synthesis activities to incorporate our current understanding of terrestrial vegetation in global water cycle models.

Dynamics of soil CO 2 efflux under varying atmospheric CO 2 concentrations reveal dominance of slow processes - Dohyoung Kim; Ram Oren; James S. Clark; Sari Palmroth; A. Christopher Oishi; Heather R. McCarthy; Chris A. Maier; Kurt Johnsen (Global Change Biology, 2017)
We evaluated the effect on soil CO 2 efflux ( F CO 2 ) of sudden changes in photosynthetic rates by altering CO 2 concentration in plots subjected to +200 ppmv for 15 years. Five‐day intervals of exposure to elevated CO 2 ( eCO 2 ) ranging 1.0–1.8 times ambient did not affect F CO 2 . F CO 2 did not decrease until 4 months after termination of the long‐term eCO 2 treatment, longer than the 10 days observed for decrease of F CO 2 after experimental blocking of C flow to belowground, but shorter than the ~13 months it took for increase of F CO 2 following the initiation of eCO 2 . The reduction of F CO 2 upon termination of enrichment (~35%) cannot be explained by the reduction of leaf area (~15%) and associated carbohydrate production and allocation, suggesting a disproportionate contraction of the belowground ecosystem components; this was consistent with the reductions in base respiration and F CO 2 ‐temperature sensitivity. These asymmetric responses pose a tractable challenge to process‐based models attempting to isolate the effect of individual processes on F CO2 .

Informing climate models with rapid chamber measurements of forest carbon uptake - Daniel B. Metcalfe; Daniel Ricciuto; Sari Palmroth; Catherine Campbell; Vaughan Hurry; Jiafu Mao; Sonja G. Keel; Sune Linder; Xiaoying Shi; Torgny Näsholm; Klas E. A. Ohlsson; M. Blackburn; et al. (Global Change Biology, 2017)
Models predicting ecosystem carbon dioxide ( CO 2 ) exchange under future climate change rely on relatively few real‐world tests of their assumptions and outputs. Here, we demonstrate a rapid and cost‐effective method to estimate CO 2 exchange from intact vegetation patches under varying atmospheric CO 2 concentrations . We find that net ecosystem CO 2 uptake ( NEE ) in a boreal forest rose linearly by 4.7 ± 0.2% of the current ambient rate for every 10 ppm CO 2 increase, with no detectable influence of foliar biomass, season, or nitrogen (N) fertilization. The lack of any clear short‐term NEE response to fertilization in such an N‐limited system is inconsistent with the instantaneous downregulation of photosynthesis formalized in many global models. Incorporating an alternative mechanism with considerable empirical support – diversion of excess carbon to storage compounds – into an existing earth system model brings the model output into closer agreement with our field measurements. A global simulation incorporating this modified model reduces a long‐standing mismatch between the modeled and observed seasonal amplitude of atmospheric CO 2 . Wider application of this chamber approach would provide critical data needed to further improve modeled projections of biosphere–atmosphere CO 2 exchange in a changing climate.

Analysis of the bacteriorhodopsin-producing haloarchaea reveals a core community that is stable over time in the salt crystallizers of Eilat, Israel - Nikhil Ram-Mohan; Aharon Oren; R. Thane Papke (Extremophiles, 2016)

Greater carbon allocation to mycorrhizal fungi reduces tree nitrogen uptake in a boreal forest - Niles J. Hasselquist; Daniel B. Metcalfe; Erich Inselsbacher; Zsofia Stangl; Ram Oren; Torgny Näsholm; Peter Högberg (Ecology, 2016)
The central role that ectomycorrhizal ( EM ) symbioses play in the structure and function of boreal forests pivots around the common assumption that carbon (C) and nitrogen (N) are exchanged at rates favorable for plant growth. However, this may not always be the case. It has been hypothesized that the benefits mycorrhizal fungi convey to their host plants strongly depends upon the availability of C and N, both of which are rapidly changing as a result of intensified human land use and climate change. Using large‐scale shading and N addition treatments, we assessed the independent and interactive effects of changes in C and N supply on the transfer of N in intact EM associations with ~15 yr. old Scots pine trees. To assess the dynamics of N transfer in EM symbioses, we added trace amounts of highly enriched 15 NO 3 ‐ label to the EM ‐dominated mor‐layer and followed the fate of the 15 N label in tree foliage, fungal chitin on EM root tips, and EM sporocarps. Despite no change in leaf biomass, shading resulted in reduced tree C uptake, ca . 40% lower fungal biomass on EM root tips, and greater 15 N label in tree foliage compared to unshaded control plots, where more 15 N label was found in fungal biomass on EM colonized root tips. Short‐term addition of N shifted the incorporation of 15 N label from EM fungi to tree foliage, despite no significant changes in below‐ground tree C allocation to EM fungi. Contrary to the common assumption that C and N are exchanged at rates favorable for plant growth, our results show for the first time that under N‐limited conditions greater C allocation to EM fungi in the field results in reduced, not increased, N transfer to host trees. Moreover, given the ubiquitous nature of mycorrhizal symbioses, our results stress the need to incorporate mycorrhizal dynamics into process‐based ecosystem models to better predict forest C and N cycles in light of global climate change.

Response to CO 2 enrichment of understory vegetation in the shade of forests - Dohyoung Kim; Ram Oren; Song S. Qian (Global Change Biology, 2016)
Responses of forest ecosystems to increased atmospheric CO 2 concentration have been studied in few free‐air CO 2 enrichment ( FACE ) experiments during last two decades. Most studies focused principally on the overstory trees with little attention given to understory vegetation. Despite its small contribution to total productivity of an ecosystem, understory vegetation plays an important role in predicting successional dynamics and future plant community composition. Thus, the response of understory vegetation in Pinus taeda plantation at the Duke Forest FACE site after 15–17 years of exposure to elevated CO 2 , 6–13 of which with nitrogen (N) amendment, was examined. Aboveground biomass and density of the understory decreased across all treatments with increasing overstory leaf area index ( LAI ). However, the CO 2 and N treatments had no effect on aboveground biomass, tree density, community composition, and the fraction of shade‐tolerant species. The increases of overstory LAI (~28%) under elevated CO 2 resulted in a reduction of light available to the understory (~18%) sufficient to nullify the expected growth‐enhancing effect of elevated CO 2 on understory vegetation.

Sustained effects of atmospheric [ CO 2 ] and nitrogen availability on forest soil CO 2 efflux - A. Christopher Oishi; Sari Palmroth; Kurt H. Johnsen; Heather R. McCarthy; Ram Oren (Global Change Biology, 2014)
Soil CO 2 efflux ( F soil ) is the largest source of carbon from forests and reflects primary productivity as well as how carbon is allocated within forest ecosystems. Through early stages of stand development, both elevated [ CO 2 ] and availability of soil nitrogen (N; sum of mineralization, deposition, and fixation) have been shown to increase gross primary productivity, but the long‐term effects of these factors on F soil are less clear. Expanding on previous studies at the Duke Free‐Air CO 2 Enrichment ( FACE ) site, we quantified the effects of elevated [ CO 2 ] and N fertilization on F soil using daily measurements from automated chambers over 10 years. Consistent with previous results, compared to ambient unfertilized plots, annual F soil increased under elevated [ CO 2 ] (ca. 17%) and decreased with N (ca. 21%). N fertilization under elevated [ CO 2 ] reduced F soil to values similar to untreated plots. Over the study period, base respiration rates increased with leaf productivity, but declined after productivity saturated. Despite treatment‐induced differences in aboveground biomass, soil temperature and water content were similar among treatments. Interannually, low soil water content decreased annual F soil from potential values – estimated based on temperature alone assuming nonlimiting soil water content – by ca. 0.7% per 1.0% reduction in relative extractable water. This effect was only slightly ameliorated by elevated [ CO 2 ]. Variability in soil N availability among plots accounted for the spatial variability in F soil , showing a decrease of ca. 114 g C m −2 yr −1 per 1 g m −2 increase in soil N availability, with consistently higher F soil in elevated [ CO 2 ] plots ca. 127 g C per 100 ppm [ CO 2 ] over the +200 ppm enrichment. Altogether, reflecting increased belowground carbon partitioning in response to greater plant nutritional needs, the effects of elevated [ CO 2 ] and N fertilization on F soil in this stand are sustained beyond the early stages of stand development and through stabilization of annual foliage production.

Forest water use and water use efficiency at elevated CO 2 : a model‐data intercomparison at two contrasting temperate forest FACE sites - Martin G. De Kauwe; Belinda E. Medlyn; Sönke Zaehle; Anthony P. Walker; Michael C. Dietze; Thomas Hickler; Atul K. Jain; Yiqi Luo; William J. Parton; I. Colin Prentice; Benjamin Smith; Peter E. Thornton; et al. (Global Change Biology, 2013)
Predicted responses of transpiration to elevated atmospheric CO 2 concentration ( eCO 2 ) are highly variable amongst process‐based models. To better understand and constrain this variability amongst models, we conducted an intercomparison of 11 ecosystem models applied to data from two forest free‐air CO 2 enrichment ( FACE ) experiments at Duke University and Oak Ridge National Laboratory. We analysed model structures to identify the key underlying assumptions causing differences in model predictions of transpiration and canopy water use efficiency. We then compared the models against data to identify model assumptions that are incorrect or are large sources of uncertainty. We found that model‐to‐model and model‐to‐observations differences resulted from four key sets of assumptions, namely (i) the nature of the stomatal response to elevated CO 2 (coupling between photosynthesis and stomata was supported by the data); (ii) the roles of the leaf and atmospheric boundary layer (models which assumed multiple conductance terms in series predicted more decoupled fluxes than observed at the broadleaf site); (iii) the treatment of canopy interception (large intermodel variability, 2–15%); and (iv) the impact of soil moisture stress (process uncertainty in how models limit carbon and water fluxes during moisture stress). Overall, model predictions of the CO 2 effect on WUE were reasonable (intermodel μ = approximately 28% ± 10%) compared to the observations (μ = approximately 30% ± 13%) at the well‐coupled coniferous site (Duke), but poor (intermodel μ = approximately 24% ± 6%; observations μ = approximately 38% ± 7%) at the broadleaf site (Oak Ridge). The study yields a framework for analysing and interpreting model predictions of transpiration responses to eCO 2 , and highlights key improvements to these types of models.

Simple additive effects are rare: a quantitative review of plant biomass and soil process responses to combined manipulations of CO 2 and temperature - Wouter I. J. Dieleman; Sara Vicca; Feike A. Dijkstra; Frank Hagedorn; Mark J. Hovenden; Klaus S. Larsen; Jack A. Morgan; Astrid Volder; Claus Beier; Jeffrey S. Dukes; John King; Sebastian Leuzinger; et al. (Global Change Biology, 2012)
In recent years, increased awareness of the potential interactions between rising atmospheric CO 2 concentrations ([ CO 2 ]) and temperature has illustrated the importance of multifactorial ecosystem manipulation experiments for validating Earth System models. To address the urgent need for increased understanding of responses in multifactorial experiments, this article synthesizes how ecosystem productivity and soil processes respond to combined warming and [ CO 2 ] manipulation, and compares it with those obtained in single factor [ CO 2 ] and temperature manipulation experiments. Across all combined elevated [ CO 2 ] and warming experiments, biomass production and soil respiration were typically enhanced. Responses to the combined treatment were more similar to those in the [ CO 2 ]‐only treatment than to those in the warming‐only treatment. In contrast to warming‐only experiments, both the combined and the [ CO 2 ]‐only treatments elicited larger stimulation of fine root biomass than of aboveground biomass, consistently stimulated soil respiration, and decreased foliar nitrogen (N) concentration. Nonetheless, mineral N availability declined less in the combined treatment than in the [ CO 2 ]‐only treatment, possibly due to the warming‐induced acceleration of decomposition, implying that progressive nitrogen limitation ( PNL ) may not occur as commonly as anticipated from single factor [ CO 2 ] treatment studies. Responses of total plant biomass, especially of aboveground biomass, revealed antagonistic interactions between elevated [ CO 2 ] and warming, i.e. the response to the combined treatment was usually less‐than‐additive. This implies that productivity projections might be overestimated when models are parameterized based on single factor responses. Our results highlight the need for more (and especially more long‐term) multifactor manipulation experiments. Because single factor CO 2 responses often dominated over warming responses in the combined treatments, our results also suggest that projected responses to future global warming in Earth System models should not be parameterized using single factor warming experiments.

Elevated CO 2 affects photosynthetic responses in canopy pine and subcanopy deciduous trees over 10 years: a synthesis from D uke FACE - David S. Ellsworth; Richard Thomas; Kristine Y. Crous; Sari Palmroth; Eric Ward; Chris Maier; Evan DeLucia; Ram Oren (Global Change Biology, 2012)
Leaf responses to elevated atmospheric CO 2 concentration (C a ) are central to models of forest CO 2 exchange with the atmosphere and constrain the magnitude of the future carbon sink. Estimating the magnitude of primary productivity enhancement of forests in elevated C a requires an understanding of how photosynthesis is regulated by diffusional and biochemical components and up‐scaled to entire canopies. To test the sensitivity of leaf photosynthesis and stomatal conductance to elevated C a in time and space, we compiled a comprehensive dataset measured over 10 years for a temperate pine forest of P inus taeda , but also including deciduous species, primarily L iquidambar styraciflua . We combined over one thousand controlled‐response curves of photosynthesis as a function of environmental drivers (light, air C a and temperature) measured at canopy heights up to 20 m over 11 years (1996–2006) to generate parameterizations for leaf‐scale models for the D uke free‐air CO 2 enrichment ( FACE ) experiment. The enhancement of leaf net photosynthesis ( A net ) in P . taeda by elevated C a of +200 μmol mol −1 was 67% for current‐year needles in the upper crown in summer conditions over 10 years. Photosynthetic enhancement of P . taeda at the leaf‐scale increased by two‐fold from the driest to wettest growing seasons. Current‐year pine foliage A net was sensitive to temporal variation, whereas previous‐year foliage A net was less responsive and overall showed less enhancement (+30%). Photosynthetic downregulation in overwintering upper canopy pine needles was small at average leaf N ( N area ), but statistically significant. In contrast, co‐dominant and subcanopy L . styraciflua trees showed A net enhancement of 62% and no A net – N area adjustments. Various understory deciduous tree species showed an average A net enhancement of 42%. Differences in photosynthetic responses between overwintering pine needles and subcanopy deciduous leaves suggest that increased C a has the potential to enhance the mixed‐species composition of planted pine stands and, by extension, naturally regenerating pine‐dominated stands.

Interannual Invariability of Forest Evapotranspiration and Its Consequence to Water Flow Downstream - A. Christopher Oishi; Ram Oren; Kimberly A. Novick; Sari Palmroth; Gabriel G. Katul (Ecosystems, 2010)

Greater seed production in elevated CO 2 is not accompanied by reduced seed quality in Pinus taeda L. - DANIELLE A. WAY; SHANNON L. LADEAU; HEATHER R. MCCARTHY; JAMES S. CLARK; RAM OREN; ADRIEN C. FINZI; ROBERT B. JACKSON (Global Change Biology, 2010)
For herbaceous species, elevated CO 2 often increases seed production but usually leads to decreased seed quality. However, the effects of increased atmospheric CO 2 on tree fecundity remain uncertain, despite the importance of reproduction to the composition of future forests. We determined how seed quantity and quality differed for pine trees grown for 12 years in ambient and elevated (ambient+200 μL L −1 ) CO 2 , at the Duke Forest free‐air CO 2 enrichment (FACE) site. We also compared annual reproductive effort with yearly measurements of aboveground net primary productivity (ANPP), precipitation (P), potential evapotranspiration (PET) and water availability [precipitation minus potential evapotranspiration (P−PET)] to investigate factors that may drive interannual variation in seed production. The number of mature, viable seeds doubled per unit basal area in high‐CO 2 plots from 1997 to 2008 ( P 2 effect on mean seed mass, viability, or nutrient content. Interannual variation in seed production was positively related to ANPP, with a similar percentage of ANPP diverted to reproduction across years. Seed production was negatively related to PET ( P P P =0.88). This study adds to the few findings that, unlike herbaceous crops, woody plants may benefit from future atmospheric CO 2 by producing larger numbers of seeds without suffering degraded seed quality. Differential reproductive responses between functional groups and species could facilitate woody invasions or lead to changes in forest community composition as CO 2 rises.

Latitudinal patterns of magnitude and interannual variability in net ecosystem exchange regulated by biological and environmental variables - WENPING YUAN; YIQI LUO; ANDREW D. RICHARDSON; RAM OREN; SEBASTIAAN LUYSSAERT; IVAN A. JANSSENS; REINHART CEULEMANS; XUHUI ZHOU; THOMAS GRÜNWALD; MARC AUBINET; CHRISTIAN BERHOFER; DENNIS D. BALDOCCHI; et al. (Global Change Biology, 2009)
Over the last two and half decades, strong evidence showed that the terrestrial ecosystems are acting as a net sink for atmospheric carbon. However the spatial and temporal patterns of variation in the sink are not well known. In this study, we examined latitudinal patterns of interannual variability (IAV) in net ecosystem exchange (NEE) of CO 2 based on 163 site‐years of eddy covariance data, from 39 northern‐hemisphere research sites located at latitudes ranging from ∼29°N to ∼64°N. We computed the standard deviation of annual NEE integrals at individual sites to represent absolute interannual variability (AIAV), and the corresponding coefficient of variation as a measure of relative interannual variability (RIAV). Our results showed decreased trends of annual NEE with increasing latitude for both deciduous broadleaf forests and evergreen needleleaf forests. Gross primary production (GPP) explained a significant proportion of the spatial variation of NEE across evergreen needleleaf forests, whereas, across deciduous broadleaf forests, it is ecosystem respiration (Re). In addition, AIAV in GPP and Re increased significantly with latitude in deciduous broadleaf forests, but AIAV in GPP decreased significantly with latitude in evergreen needleleaf forests. Furthermore, RIAV in NEE, GPP, and Re appeared to increase significantly with latitude in deciduous broadleaf forests, but not in evergreen needleleaf forests. Correlation analyses showed air temperature was the primary environmental factor that determined RIAV of NEE in deciduous broadleaf forest across the North American sites, and none of the chosen climatic factors could explain RIAV of NEE in evergreen needleleaf forests. Mean annual NEE significantly increased with latitude in grasslands. Precipitation was dominant environmental factor for the spatial variation of magnitude and IAV in GPP and Re in grasslands.

Forest fine‐root production and nitrogen use under elevated CO 2 : contrasting responses in evergreen and deciduous trees explained by a common principle - OSKAR FRANKLIN; ROSS E. McMURTRIE; COLLEEN M. IVERSEN; KRISTINE Y. CROUS; ADRIEN C. FINZI; DAVID T. TISSUE; DAVID S. ELLSWORTH; RAM OREN; RICHARD J. NORBY (Global Change Biology, 2009)
Despite the importance of nitrogen (N) limitation of forest carbon (C) sequestration at rising atmospheric CO 2 concentration, the mechanisms responsible are not well understood. To elucidate the interactive effects of elevated CO 2 (eCO 2 ) and soil N availability on forest productivity and C allocation, we hypothesized that (1) trees maximize fitness by allocating N and C to maximize their net growth and (2) that N uptake is controlled by soil N availability and root exploration for soil N. We tested this model using data collected in Free‐Air CO 2 Enrichment sites dominated by evergreen ( Pinus taeda ; Duke Forest) and deciduous [ Liquidambar styraciflua ; Oak Ridge National Laboratory (ORNL)] trees. The model explained 80–95% of variation in productivity and N‐uptake data among eCO 2 , N fertilization and control treatments over 6 years. The model explains why fine‐root production increased, and why N uptake increased despite reduced soil N availability under eCO 2 at ORNL and Duke. In agreement with observations at other sites, the model predicts that soil N availability reduced below a critical level diminishes all eCO 2 responses. At Duke, a negative feedback between reduced soil N availability and N uptake prevented progressive reduction in soil N availability at eCO 2 . At ORNL, soil N availability progressively decreased because it did not trigger reductions in N uptake; N uptake was maintained at ORNL through a large increase in the production of fast turnover fine roots. This implies that species with fast root turnover could be more prone to progressive N limitation of carbon sequestration in woody biomass than species with slow root turnover, such as evergreens. However, longer term data are necessary for a thorough evaluation of this hypothesis. The success of the model suggests that the principle of maximization of net growth to control growth and allocation could serve as a basis for simplification and generalization of larger scale forest and ecosystem models, for example by removing the need to specify parameters for relative foliage/stem/root allocation.

Role of vegetation in determining carbon sequestration along ecological succession in the southeastern United States - PAUL C. STOY; GABRIEL G. KATUL; MARIO B. S. SIQUEIRA; JEHN‐YIH JUANG; KIMBERLY A. NOVICK; HEATHER R. McCARTHY; A. CHRISTOPHER OISHI; RAM OREN (Global Change Biology, 2008)
Vegetation plays a central role in controlling terrestrial carbon (C) exchange, but quantifying its impacts on C cycling on time scales of ecological succession is hindered by a lack of long‐term observations. The net ecosystem exchange of carbon (NEE) was measured for several years in adjacent ecosystems that represent distinct phases of ecological succession in the southeastern USA. The experiment was designed to isolate the role of vegetation – apart from climate and soils – in controlling biosphere–atmosphere fluxes of CO 2 and water vapor. NEE was near zero over 5 years at an early successional old‐field ecosystem (OF). However, mean annual NEE was nearly equal, approximately −450 g C m −2 yr −1 , at an early successional planted pine forest (PP) and a late successional hardwood forest (HW) due to the sensitivity of the former to drought and ice storm damage. We hypothesize that these observations can be explained by the relationships between gross ecosystem productivity (GEP), ecosystem respiration (RE) and canopy conductance, and long‐term shifts in ecosystem physiology in response to climate to maintain near‐constant ecosystem‐level water‐use efficiency (EWUE). Data support our hypotheses, but future research should examine if GEP and RE are causally related or merely controlled by similar drivers. At successional time scales, GEP and RE observations generally followed predictions from E. P. Odum's ‘Strategy of Ecosystem Development’, with the surprising exception that the relationship between GEP and RE resulted in large NEE at the late successional HW. A practical consequence of this research suggests that plantation forestry may confer no net benefit over the conservation of mature forests for C sequestration.

Fine root dynamics in a loblolly pine forest are influenced by free‐air‐CO 2 ‐enrichment: a six‐year‐minirhizotron study - SETH G. PRITCHARD; ALLAN E. STRAND; M. LUKE McCORMACK; MICHEAL A. DAVIS; ADRIEN C. FINZI; ROBERT B. JACKSON; ROSER MATAMALA; HUGO H. ROGERS; RAM OREN (Global Change Biology, 2008)
Efforts to characterize carbon (C) cycling among atmosphere, forest canopy, and soil C pools are hindered by poorly quantified fine root dynamics. We characterized the influence of free‐air‐CO 2 ‐enrichment (ambient +200 ppm) on fine roots for a period of 6 years (Autumn 1998 through Autumn 2004) in an 18‐year‐old loblolly pine ( Pinus taeda ) plantation near Durham, NC, USA using minirhizotrons. Root production and mortality were synchronous processes that peaked most years during spring and early summer. Seasonality of fine root production and mortality was not influenced by atmospheric CO 2 availability. Averaged over all 6 years of the study, CO 2 enrichment increased average fine root standing crop (+23%), annual root length production (+25%), and annual root length mortality (+36%). Larger increase in mortality compared with production with CO 2 enrichment is explained by shorter average fine root lifespans in elevated plots (500 days) compared with controls (574 days). The effects of CO 2 ‐enrichment on fine root proliferation tended to shift from shallow (0–15 cm) to deeper soil depths (15–30) with increasing duration of the study. Diameters of fine roots were initially increased by CO 2 ‐enrichment but this effect diminished over time. Averaged over 6 years, annual fine root NPP was estimated to be 163 g dw m −2 yr −1 in CO 2 ‐enriched plots and 130 g dw m −2 yr −1 in control plots ( P = 0.13) corresponding to an average annual additional input of fine root biomass to soil of 33 g m −2 yr −1 in CO 2 ‐enriched plots. A lack of consistent CO 2 × year effects suggest that the positive effects of CO 2 enrichment on fine root growth persisted 6 years following minirhizotron tube installation (8 years following initiation of the CO 2 fumigation). Although CO 2 ‐enrichment contributed to extra flow of C into soil in this experiment, the magnitude of the effect was small suggesting only modest potential for fine root processes to directly contribute to soil C storage in south‐eastern pine forests.

Temporal dynamics and spatial variability in the enhancement of canopy leaf area under elevated atmospheric CO 2 - HEATHER R. McCARTHY; RAM OREN; ADRIEN C. FINZI; DAVID S. ELLSWORTH; HYUN‐SEOK KIM; KURT H. JOHNSEN; BONNIE MILLAR (Global Change Biology, 2007)
Increased canopy leaf area ( L ) may lead to higher forest productivity and alter processes such as species dynamics and ecosystem mass and energy fluxes. Few CO 2 enrichment studies have been conducted in closed canopy forests and none have shown a sustained enhancement of L . We reconstructed 8 years (1996–2003) of L at Duke's Free Air CO 2 Enrichment experiment to determine the effects of elevated atmospheric CO 2 concentration ([CO 2 ]) on L before and after canopy closure in a pine forest with a hardwood component, focusing on interactions with temporal variation in water availability and spatial variation in nitrogen (N) supply. The dynamics of L were reconstructed using data on leaf litterfall mass and specific leaf area for hardwoods, and needle litterfall mass and specific leaf area combined with needle elongation rates, and fascicle and shoot counts for pines. The dynamics of pine L production and senescence were unaffected by elevated [CO 2 ], although L senescence for hardwoods was slowed. Elevated [CO 2 ] enhanced pine L and the total canopy L (combined pine and hardwood species; P L and its response to elevated [CO 2 ] was not random. Each year pine L under ambient and elevated [CO 2 ] was spatially correlated to the variability in site nitrogen availability (e.g. r 2 =0.94 and 0.87 in 2001, when L was highest before declining due to droughts and storms), with the [CO 2 ]‐induced enhancement increasing with N ( P =0.061). Incorporating data on N beyond the range of native fertility, achieved through N fertilization, indicated that pine L had reached the site maximum under elevated [CO 2 ] where native N was highest. Thus closed canopy pine forests may be able to increase leaf area under elevated [CO 2 ] in moderate fertility sites, but are unable to respond to [CO 2 ] in both infertile sites (insufficient resources) and sites having high levels of fertility (maximum utilization of resources). The total canopy L , representing the combined L of pine and hardwood species, was constant across the N gradient under both ambient and elevated [CO 2 ], generating a constant enhancement of canopy L . Thus, in mixed species stands, L of canopy hardwoods which developed on lower fertility sites (∼3 g N inputs m −2 yr −1 ) may be sufficiently enhanced under elevated [CO 2 ] to compensate for the lack of response in pine L , and generate an appreciable response of total canopy L (∼14%).

Eco‐hydrological controls on summertime convective rainfall triggers - JEHN‐YIH JUANG; GABRIEL G. KATUL; AMILCARE PORPORATO; PAUL C. STOY; MARIO S. SIQUEIRA; MATTEO DETTO; HYUN‐SEOK KIM; RAM OREN (Global Change Biology, 2007)
Triggers of summertime convective rainfall depend on numerous interactions and feedbacks, often compounded by spatial variability in soil moisture and its impacts on vegetation function, vegetation composition, terrain, and all the complex turbulent entrainment processes near the capping inversion. To progress even within the most restricted and idealized framework, many of the governing processes must be simplified and parameterized. In this work, a zeroth‐order representation of the dynamical processes that control convective rainfall triggers – namely land surface fluxes of heat and moisture – is proposed and used to develop a semianalytical model to explore how differential sensitivities of various ecosystems to soil moisture states modify convective rainfall triggers. The model is then applied to 4 years (2001–2004) of half‐hourly precipitation, soil moisture, environmental, and eddy‐covariance surface heat flux data collected at a mixed hardwood forest (HW), a maturing planted loblolly pine forest (PP), and an abandoned old field (OF) experiencing the same climatic and edaphic conditions. We found that the sensitivity of PP to soil moisture deficit enhances the trigger of convective rainfall relative to HW and OF, with enhancements of about 25% and 30% for dry moisture states, and 5% and 15% for moist soil moisture states, respectively. We discuss the broader implications of these findings on potential modulations of convective rainfall triggers induced by projected large‐scale changes in timberland composition within the Southeastern United States.

Eco-hydrological controls on summertime convective rainfall triggers - JEHN-YIH JUANG; GABRIEL G. KATUL; AMILCARE PORPORATO; PAUL C. STOY; MARIO S. SIQUEIRA; MATTEO DETTO; HYUN-SEOK KIM; RAM OREN (Global Change Biology, 2007)

Separating the effects of climate and vegetation on evapotranspiration along a successional chronosequence in the southeastern US - PAUL C. STOY; GABRIEL G. KATUL; MARIO B. S. SIQUEIRA; JEHN‐YIH JUANG; KIMBERLY A. NOVICK; HEATHER R. McCARTHY; A. CHRISTOPHER OISHI; JOSHUA M. UEBELHERR; HYUN‐SEOK KIM; RAM OREN (Global Change Biology, 2006)
We combined Eddy‐covariance measurements with a linear perturbation analysis to isolate the relative contribution of physical and biological drivers on evapotranspiration (ET) in three ecosystems representing two end‐members and an intermediate stage of a successional gradient in the southeastern US (SE). The study ecosystems, an abandoned agricultural field [old field (OF)], an early successional planted pine forest (PP), and a late‐successional hardwood forest (HW), exhibited differential sensitivity to the wide range of climatic and hydrologic conditions encountered over the 4‐year measurement period, which included mild and severe droughts and an ice storm. ET and modeled transpiration differed by as much as 190 and 270 mm yr −1 , respectively, between years for a given ecosystem. Soil water supply, rather than atmospheric demand, was the principal external driver of interannual ET differences. ET at OF was sensitive to climatic variability, and results showed that decreased leaf area index ( L ) under mild and severe drought conditions reduced growing season (GS) ET (ET GS ) by ca. 80 mm compared with a year with normal precipitation. Under wet conditions, higher intrinsic stomatal conductance ( g s ) increased ET GS by 50 mm. ET at PP was generally larger than the other ecosystems and was highly sensitive to climate; a 50 mm decrease in ET GS due to the loss of L from an ice storm equaled the increase in ET from high precipitation during a wet year. In contrast, ET at HW was relatively insensitive to climatic variability. Results suggest that recent management trends toward increasing the land‐cover area of PP‐type ecosystems in the SE may increase the sensitivity of ET to climatic variability.

Estimating the uncertainty in annual net ecosystem carbon exchange: spatial variation in turbulent fluxes and sampling errors in eddy‐covariance measurements - RAM OREN; CHENG‐I HSIEH; PAUL STOY; JOHN ALBERTSON; HEATHER R MCCARTHY; PETER HARRELL; GABRIEL G KATUL (Global Change Biology, 2006)
Above forest canopies, eddy covariance (EC) measurements of mass (CO 2 , H 2 O vapor) and energy exchange, assumed to represent ecosystem fluxes, are commonly made at one point in the roughness sublayer (RSL). A spatial variability experiment, in which EC measurements were made from six towers within the RSL in a uniform pine plantation, quantified large and dynamic spatial variation in fluxes. The spatial coefficient of variation (CV) of the scalar fluxes decreased with increasing integration time, stabilizing at a minimum that was independent of further lengthening the averaging period (hereafter a ‘stable minimum’). For all three fluxes, the stable minimum (CV=9–11%) was reached at averaging times ( τ p ) of 6–7 h during daytime, but higher stable minima (CV=46–158%) were reached at longer τ p (>12 h) during nighttime. To the extent that decreasing CV of EC fluxes reflects reduction in micrometeorological sampling errors, half of the observed variability at τ p =30 min is attributed to sampling errors. The remaining half (indicated by the stable minimum CV) is attributed to underlying variability in ecosystem structural properties, as determined by leaf area index, and perhaps associated ecosystem activity attributes. We further assessed the spatial variability estimates in the context of uncertainty in annual net ecosystem exchange (NEE). First, we adjusted annual NEE values obtained at our long‐term observation tower to account for the difference between this tower and the mean of all towers from this experiment; this increased NEE by up to 55 g C m −2 yr −1 . Second, we combined uncertainty from gap filling and instrument error with uncertainty because of spatial variability, producing an estimate of variability in annual NEE ranging from 79 to 127 g C m −2 yr −1 . This analysis demonstrated that even in such a uniform pine plantation, in some years spatial variability can contribute ∼50% of the uncertainty in annual NEE estimates.

Temporal variability in 13C of respired CO2 in a pine and a hardwood forest subject to similar climatic conditions - Behzad Mortazavi; Jeffrey P. Chanton; James L. Prater; A. Christopher Oishi; Ram Oren; Gabriel Katul (Oecologia, 2005)

Exposure to an enriched CO 2 atmosphere alters carbon assimilation and allocation in a pine forest ecosystem - Karina V. R. Schäfer; Ram Oren; David S. Ellsworth; Chun‐Ta Lai; Jeffrey D. Herrick; Adrien C. Finzi; Daniel D. Richter; Gabriel G. Katul (Global Change Biology, 2003)
We linked a leaf‐level CO 2 assimilation model with a model that accounts for light attenuation in the canopy and measurements of sap‐flux‐based canopy conductance into a new canopy conductance‐constrained carbon assimilation (4C‐A) model. We estimated canopy CO 2 uptake ( A nC ) at the Duke Forest free‐air CO 2 enrichment (FACE) study. Rates of A nC estimated from the 4C‐A model agreed well with leaf gas exchange measurements ( A net ) in both CO 2 treatments. Under ambient conditions, monthly sums of net CO 2 uptake by the canopy ( A nC ) were 13% higher than estimates based on eddy‐covariance and chamber measurements. Annual estimates of A nC were only 3% higher than carbon (C) accumulations and losses estimated from ground‐based measurements for the entire stand. The C budget for the Pinus taeda component was well constrained (within 1% of ground‐based measurements). Although the closure of the C budget for the broadleaf species was poorer (within 20%), these species are a minor component of the forest. Under elevated CO 2 , the C used annually for growth, turnover, and respiration balanced only 80% of the A nC . Of the extra 700 g C m −2 a −1 (1999 and 2000 average), 86% is attributable to surface soil CO 2 efflux. This suggests that the production and turnover of fine roots was underestimated or that mycorrhizae and rhizodeposition became an increasingly important component of the C balance. Under elevated CO 2 , net ecosystem production increased by 272 g C m −2 a −1 : 44% greater than under ambient CO 2 . The majority (87%) of this C was sequestered in a moderately long‐term C pool in wood, with the remainder in the forest floor–soil subsystem.

Reduction of forest floor respiration by fertilization on both carbon dioxide‐enriched and reference 17‐year‐old loblolly pine stands - JOHN R. BUTNOR; KURT H. JOHNSEN; RAM OREN; GABRIEL G. KATUL (Global Change Biology, 2003)
Elevated atmospheric carbon dioxide (CO 2 e ) increases soil respiration rates in forest, grassland, agricultural and wetland systems as a result of increased growth, root biomass and enhanced biological activity of soil microorganisms. Less is known about how forest floor fluxes respond to the combined effects of elevated CO 2 and nutrient amendments; until now no experiments have been in place with large forest trees to allow even preliminary investigations. We investigated changes in forest floor respiration (S ff ) in a Pinus taeda L. plantation fumigated with CO 2 by using free‐air CO 2 enrichment (FACE) technology and given nutrient amendments. The prototype FACE apparatus (FACEp; 707 m 2 ) was constructed in 1993, 10 years after planting, on a moderate fertility site in Duke Forest, North Carolina, USA, enriching the stand to 55 Pa (CO 2 e ). A nearby ambient CO 2 (CO 2 a ) plot (117 m 2 ) was designated at the inception of the study as a reference (Ref). Both FACEp and Ref plot were divided in half and urea fertilizer was applied to one half at an annual rate of 11.2 g N m −2 in the spring of 1998, 1999 and 2000. Forest floor respiration was monitored continuously for 220 days – March through November 2000 – by using two Automated Carbon Efflux Systems. Thirty locations (491 cm 2 each) were sampled in both FACEp and Ref, about half in each fertility treatment. Forest floor respiration was strongly correlated with soil temperature at 5 cm. Rates of S ff were greater in CO 2 e relative to CO 2 a (an enhancement of ∼178 g C m −2 ) during the measurement period. Application of fertilizer resulted in a statistically significant depression of respiration rates in both the CO 2 a and CO 2 e plots (a reduction of ∼186 g C m −2 ). The results suggest that closed canopy forests on moderate fertility sites cycle back to the atmosphere more assimilated carbon (C) than similar forests on sites of high fertility. We recognize the limitations of this non‐replicated study, but its clear results offer strong testable hypotheses for future research in this important area.

Hydrologic balance in an intact temperate forest ecosystem under ambient and elevated atmospheric CO 2 concentration - Karina V. R. Schäfer; Ram Oren; Chun‐Ta Lai; Gabriel G. Katul (Global Change Biology, 2002)
Increasing atmospheric CO 2 concentration decreases stomatal conductance in many species, but the savings of water from reduced transpiration may permit the forest to retain greater leaf area index ( L ). Therefore, the net effect on water use in forest ecosystems under a higher CO 2 atmosphere is difficult to predict. The free air CO 2 enrichment (FACE) facility ( n = 3) in a 14‐m tall (in 1996) Pinus taeda L. stand was designed to reduce uncertainties in predicting such responses. Continuous measurements of precipitation, throughfall precipitation, sap flux, and soil moisture were made over 3.5 years under ambient (CO 2 a ) and elevated (CO 2 e ) ambient + 200 µmol mol −1 ). Annual stand transpiration under ambient CO 2 conditions accounted for 84–96% of latent heat flux measured with the eddy‐covariance technique above the canopy. Under CO 2 e , P. taeda transpired less per unit of leaf area only when soil drought was severe. Liquidambar styraciflua , the other major species in the forest, used progressively less water, settling at 25% reduction in sap flux density after 3.5 years under CO 2 e . Because P. taeda dominated the stand, and severe drought periods were of relatively short duration, the direct impact of CO 2 e on water savings in the stand was undetectable. Moreover, the forest used progressively more water under CO 2 e , probably because soil moisture availability progressively increased, probably owing to a reduction in soil evaporation caused by more litter buildup in the CO 2 e plots. The results suggest that, in this forest, the effect of CO 2 e on transpiration was greater indirectly through enhanced litter production than directly through reduced stomatal conductance. In forests composed of species more similar to L. styraciflua , water savings from stomatal closure may dominate the response to CO 2 e .

Modelling night‐time ecosystem respiration by a constrained source optimization method - Chun‐Ta Lai; Gabriel Katul; John Butnor; David Ellsworth; Ram Oren (Global Change Biology, 2002)
One of the main challenges to quantifying ecosystem carbon budgets is properly quantifying the magnitude of night‐time ecosystem respiration. Inverse Lagrangian dispersion analysis provides a promising approach to addressing such a problem when measured mean CO 2 concentration profiles and nocturnal velocity statistics are available. An inverse method, termed ‘Constrained Source Optimization’ or CSO, which couples a localized near‐field theory (LNF) of turbulent dispersion to respiratory sources, is developed to estimate seasonal and annual components of ecosystem respiration. A key advantage to the proposed method is that the effects of variable leaf area density on flow statistics are explicitly resolved via higher‐order closure principles. In CSO, the source distribution was computed after optimizing key physiological parameters to recover the measured mean concentration profile in a least‐square fashion. The proposed method was field‐tested using 1 year of 30‐min mean CO 2 concentration and CO 2 flux measurements collected within a 17‐year‐old (in 1999) even‐aged loblolly pine ( Pinus taeda L.) stand in central North Carolina. Eddy‐covariance flux measurements conditioned on large friction velocity, leaf‐level porometry and forest‐floor respiration chamber measurements were used to assess the performance of the CSO model. The CSO approach produced reasonable estimates of ecosystem respiration, which permits estimation of ecosystem gross primary production when combined with daytime net ecosystem exchange (NEE) measurements. We employed the CSO approach in modelling annual respiration of above‐ground plant components ( c. 214 g C m −2 year −1 ) and forest floor ( c. 989 g C m −2 year −1 ) for estimating gross primary production ( c. 1800 g C m −2 year −1 ) with a NEE of c. 605 g C m −2 year −1 for this pine forest ecosystem. We conclude that the CSO approach can utilise routine CO 2 concentration profile measurements to corroborate forest carbon balance estimates from eddy‐covariance NEE and chamber‐based component flux measurements.

Transpiration in response to variation in microclimate and soil moisture in southeastern deciduous forests - Ram Oren; Diane E. Pataki (Oecologia, 2001)

Modelling Vegetation-Atmosphere Co2 Exchange By A Coupled Eulerian-Langrangian Approach - Chun-Ta Lai; Gabriel Katul; David Ellsworth; Ram Oren (Boundary-Layer Meteorology, 2000)

Spatial Variability of Turbulent Fluxes in the Roughness Sublayer of an Even-Aged Pine Forest - Gabriel Katul; Cheng-I Hsieh; David Bowling; Kenneth Clark; Narasinha Shurpali; Andrew Turnipseed; John Albertson; Kevin Tu; Dave Hollinger; Bob Evans; Brian Offerle; Dean Anderson; et al. (Boundary-Layer Meteorology, 1999)

Elevated carbon dioxide does not affect average canopy stomatal conductance of Pinus taeda L. - Diane E. Pataki; Ram Oren; David T. Tissue (Oecologia, 1998)